Kyrgyz Republic : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Kyrgyz Republic. (IMF Staff Country Reports; Country Report, 2007)
The staff report for the Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility on the Kyrgyz Republic highlights recent economic developments and performance. The current account deficit continued to widen on account of higher imports driven by strong demand, but was more than financed by private capital inflows. Policy discussions focused on the challenges posed by the sharp uptick in inflation in the context of exogenous shocks and global financial turbulence. Continued fiscal restraint is important both for reducing inflation and for enhancing debt sustainability.